Students' attitudes towards didactic characteristics in graphic design classes - Kač Nemanič, Martina (Revija za elementarno izobraževanje, 2019)
Contemporary education enables the development of creative expression in students, while the role and significance of didactic approaches in secondary school have not yet been comprehensively studied. The article presents the results of research into students' attitudes towards didactic characteristics of Graphic Design classes in secondary school. We were interested in the attitude of 3rd-year students (17-18 years old) towards the characteristics of the subject Graphic Design, and their level of satisfaction with the use of teaching methods, learning techniques and didactic communication in Slovenian schools. The results show that little attention is paid to the concept of effective methodologies in practice. There is a need for a range of didactic approaches that would contribute to active, interesting, creative and dynamically based Graphic Design classes.
Keywords: didactic characteristics; didaktične značilnosti; grafično oblikovanje; graphic design; level of satisfaction; nivo zadovoljstva; secondary school; srednja šola; stališča dijakov; students' attitudes